Morphological Metaphor Mapping of Moral Concepts in Chinese Culture - Liu, Yingjie; Li, Kang; Li, Lina; Zhang, Jing; Lin, Yuerui; DiFabrizio, Baxter; Wang, He (Frontiers in Psychology, 2020)
According to conceptual metaphor theory, individuals are thought to understand or express abstract concepts by using referents in the physical world—right and left for moral and immoral, for example. In this research, we used a modified Stroop paradigm to explore how abstract moral concepts are metaphorically translated onto physical referents in Chinese culture using the Chinese language. We presented Chinese characters related to moral and immoral abstract concepts in either non-distorted or distorted positions (Study 1) or rotated to the right or to the left (Study 2). When we asked participants to identify the Chinese characters, they more quickly and accurately identified morally positive characters if they were oriented upright or turned to the right and more quickly and accurately identified immoral characters when the characters were distorted or rotated left. These results support the idea that physical cues are used in metaphorically encoding social abstractions and moral norms and provided cross-cultural validation for conceptual metaphor theory, which would predict our results.